∫(1−cos⁡x)cosec2⁡xdx is equal to

(1cosx)cosec2xdx is equal to

  1. A

    tanx+C

  2. B

    tanx2+C

  3. C

    12tanx2+C

  4. D

    None of these

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    (1cosx)cosec2xdx=cosec2xdxcosec2xcosxdx=cotxcosecxcotxdx =cotx+cosecx+C=1cosxsinx+C =2sin2x22sinx2cosx2+C =tanx2+C 

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.